SOCIO-CULTURAL TABOOS AND THE RISE OF DIGITAL MEDIA UTILIZATION AS A SOURCE OF INFORMATION ON SEXUALITY BY UNIVERSITY STUDENTS - Qalbi, Salikha Tsamratul; Herawati, Erna (Sosiohumaniora, 2024)
Drawing on John Macionis' definition of sexuality, this study explores the increasing use of digital media as the primary source of information on sexuality among university students, driven by socio-cultural taboos surrounding discussions of sexuality and the declining role of parents in providing education and guidance on sexual matters.  It examines the impact of these socio-cultural factors and their implications for students' understanding of healthy and responsible sexuality. It also aims to provide insights for stakeholders in developing more effective and open approaches to sexual education within both family and educational institutions. This study was conducted using a mixed-method approach combining quantitative and qualitative data, involving university students in Bandung City. The result of this study suggests in many cultures, sexuality remains a sensitive and taboo subject, particularly within family settings. The lack of comprehensive parental involvement in sexual education further strengthens students' reliance on these digital resources. They seek information about sexuality through digital platforms such as websites, social media, and apps, which offer easy and anonymous access to various sources.